Dilemma of Human Resources in Public Services: An Analysis of Performance among Honorary Employees - Rikha Murliasari; Zahara Tussoleha Rony; Taslim Djafar; Hadi Peristiwo; Arif Saefudin; Khikmatul Islah (Jurnal Manajemen Pelayanan Publik, 2023)
This study proposes to examine human resource management strategies that impact the performance outcomes of non-permanent (honorary) employees in the Bandung government. Qualitative research methodology was applied to gain a comprehensive understanding. This research was conducted in the Bandung City government by conducting observations and interviews with 10 participants. Furthermore, the collected data was analyzed using Atlas.ti qualitative software. All transcribed information was scrutinised and sorted based on the research questions. Data that met the research objectives were organized into sub-categories, reflecting similar characteristics. The research findings show that the performance of honorary employees in the Bandung City government is shaped by a combination of "hard" and "soft" approaches in human resource management. Improving employee performance within the Bandung City government is a top priority for the effectiveness of public services, thus requiring further improvement and a more in-depth strategic assessment. This study proposes implementing an integrated approach that includes both "hard" and "soft" human resource management techniques and the development of a culture of continuous learning and strong management dedication.